The impact of bifacial photovoltaic module orientation on electrical energy production under the climatic conditions of Andijan (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines the process of converting solar radiation into electrical energy using bifacial photovoltaic (PV) panels. Bifacial PV panels are becoming increasingly popular for commercial and industrial applications due to their ability to generate higher energy yields per unit area compared to conventional monofacial panels. The additional energy produced from the rear side of these panels depends on several factors, including the intensity of reflected sunlight from the surrounding surfaces and the albedo of the ground. In particular, reflective surfaces such as light-colored or polished materials can significantly enhance the energy output of bifacial solar modules. The study highlights that optimizing both the installation configuration and the surface properties beneath the panels can lead to substantial improvements in overall system efficiency. These findings are important for the design and deployment of high-performance PV systems in various climatic conditions
Keywords: efficiency, bifacial solar panel, silicon, solar energy, albedo, energy yield